THE TRANSLATION STUDY OF KALĀM INSYĀ’Ī THALABĪ IN THE BOOK MATN HADITH ARBA'ĪN QUR’ĀNIYYAH: KAJIAN TERJEMAHAN KALĀM INSYĀ’I THALABĪ DALAM BUKU MATAN HADITS ARBA’ĪN QUR’ĀNIYYAH - Fauzi Hidayatulloh; Muhammad Yunus Anis (Muaddib: Journal of Arabic Language and Literature, 2025)
The book Matan Hadith Arba'īn Qur'āniyyah is a book of 40 saheeh hadiths about the virtues of reading, memorizing, studying, and teaching the Qur'an. Discuss the manners that must be possessed by the memorizers of the Qur'an and warn against taking worldly advantage of the Qur'an. This research was conducted to describe the types  of kalām insyā'i thalabī and translation techniques in the book Matan Hadith Arba'īn Qur'āniyyah. The method applied in this study is a qualitative descriptive method, while the data in this study is in the form of the translation of kalām insyā'i thalabī in the book Matan Hadith Arba'īn Qur'āniyyah. Data collection techniques are carried out by observation techniques, questionnaires, observation and recording techniques. The results of this research are as follows: The translation book of  Matan Hadith Arba'īn Qur'āniyyah has 5 types  of kalām insyā'i thalabī, namely amr, nahyi, nida', tamannī, and istifhām. Each type of kalām insyā'i thalabī is amr 20 (39.2%), nahyi 2 data (3.9%), nida' 12 data (23.5%), tamannī 2 data (3.9%), and istifhām 15 data (29.4%). The translation of kalām insyā'i thalabī in the book Matan Hadith Arbā'in Qur'āniyyah uses 11 translation techniques, namely literal 3 data (2.8%), borrowing 22 data (19.4%), kalke 6 data (6.4%), common equivalent 46 data (42.6%), amplification of 14 data (12.9%), discursive creation of 4 data (3.7%), linguistic amplification of 3 data (2.8%), description of 2 data (1.8%),  compensation of 4 data (3.8%), modulation of 1 data (1%), reduction of 3 data (2.8%).